PENGARUH NILAI PRODUK DAN KEPUASAN TERHADAP LOYALITAS PELANGGAN PADA TOKO MR.DIY CABANG LASUSUA - Andi Zaskia Ramdhani; Andi Mappatompo; Muhammad Nur Abdi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of product value and customer satisfaction on customer loyalty at Mr. DIY Lasusua Branch. The research uses a quantitative approach with an associative method, which seeks to determine the relationship and influence among variables. The population of this study consists of all customers of Mr. DIY Lasusua Branch, with a sample of 150 respondents selected using purposive sampling techniques. Data were collected through the distribution of questionnaires using a Likert scale. The data analysis techniques applied include validity testing, reliability testing, classical assumption testing, and multiple linear regression analysis, assisted by SPSS software. The results of the study indicate that product value has a positive and significant effect on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty, and, product value and customer satisfaction have a significant effect on customer loyalty at Mr. DIY Lasusua Branch.